Quality Control of Furniture Products With SQC and FMEA Methods at UD. XYZ - Erwansyah, Mohammad Septian; Aryanny, Enny (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2025)
In the era of globalization, increasingly fierce industrial competition forces companies to improve product quality and production efficiency. This study is focused on UD. XYZ iron fabrication company, which experienced a bench product defect rate of 13.68%, exceeding the intended tolerance standard of 9%. The purpose of this study is to analyze the quality control processes of bench furniture products at UD. XYZ to reduce the defect rate. For this purpose the writer used the Statistical Quality Control (SQC) and Failure Mode and Effect Analysis (FMEA) methods. Based on the data obtained, there are six types of defects that occur during the production process of furniture bench products with the largest percentage of defects being missing color (19.9%), followed by broken bench pads (19.1%), and broken rubber feet (17.7%). Based on the RPN calculation, the first highest RPN is obtained for the type of missing color defect of 210, which is caused by the lack of worker accuracy. Second, the bench pad broke at 210, which is caused by the worker being too hard when hitting the bench pad. Third, the rubber foot broke by 180 which is caused by the worker hitting the rubber foot too hard. To reduce the defect rate it is recommended for the company management to provide more supervision and training to the workers.Keywords – Failure Mode and Effect Analysis, Furniture, Statistic Quality Control, Quality Control.